Knowledge and beliefs about hepatitis B virus infection and associated factors among Chinese migrants in Australia: The result of a quantitative study. (25th November 2020) - Jin, Defeng; Brener, Loren; Treloar, Carla
Abstract: Chinese immigrants to Australia have an increased prevalence of hepatitis B virus (HBV) infection compared to the general population. Despite this, engagement with HBV screening and healthcare for chronic hepatitis B (CHB) among immigrants of Chinese background is relatively low. This study investigated knowledge about HBV among this high‐risk community and explored sociodemographic factors that might influence this knowledge. During February to September 2019, first generation Chinese immigrants from mainland China and their immediate descents residing in Sydney and Melbourne were recruited via convenience and snowball sampling and completed a survey in either English or Chinese. Survey items included HBV knowledge, attitudes towards people living with CHB and demographic information. Three hundred and ninety‐six participants completed the survey. The median HBV knowledge score was 53% correct, indicating that knowledge about HBV was low to middle range among participants. While participants had the most knowledge in the domain of perceptions and understandings of HBV, this was still low. Participants also had limited knowledge about HBV prevention, transmission and treatment. Those with higher English proficiency, post‐secondary education, lower levels of HBV‐related stigma and those who had contact with people living with CHB appeared to have greater HBV knowledge. This study showed that HBV knowledge among Chinese people originally from mainland China living in Australia is limited and even deficient in some key areas. Additionally, the relationships between HBV knowledge and particular sociodemographic variables, knowing someone living with HBV and stigma associated with HBV provides key information to assist in the development of targeted health promotion to increase HBV knowledge and change stigmatising attitudes towards HBV among the Chinese community in Australia.